Owning and renting: a public preferences in Klang / Nor Kamarina Abdul Wahab and Lizawati Abdullah - Abdul Wahab, Nor Kamarina (2023)
The desire to one day buys a home is one that practically everyone has. There are a number of issues that make renting and owning each have unique challenges. Rents have increased in most regions over the past several decades, making it harder for young people to save money. The bank's stringent mortgage standards should also be reviewed in order to accommodate first-time homebuyers, particularly young people. Additionally, putting up a sizeable down payment for a home might be a challenging task. The option of tailoring living environment is yet another important distinction between renting and buying. The study's target audience is the general population, and it was carried out in Klang, Selangor. 384 people in all took part in the study. This study's goal is to determine the public's preferences when deciding whether to buy or rent a home and to rank the top preferences. This study uses a quantitative methodology that entails utilising Google Forms to collect data through questionnaires. According to surveys, Klang residents choose owning their own home over renting. The results demonstrate that financial considerations are the most important when deciding whether to buy or rent a home. Prior to deciding whether to buy or rent a home, Klang residents would prioritise the financial aspects. This research suggests that before starting a housing project, developers find out which characteristics people would prioritise when deciding whether to buy or rent a home.